The comparative effectiveness of oral versus subcutaneous methotrexate for the treatment of early rheumatoid arthritis. Issue 6 (15th May 2015) - Hazlewood, Glen S; Thorne, J Carter; Pope, Janet E; Lin, Daming; Tin, Diane; Boire, Gilles; Haraoui, Boulos; Hitchon, Carol A; Keystone, Edward C; Jamal, Shahin; Bykerk, Vivian P
Abstract : Objective: To determine the comparative effectiveness of oral versus subcutaneous methotrexate (MTX) as initial therapy for patients with early rheumatoid arthritis (ERA). Methods: Patients with ERA (symptoms ≤1 year) initiating MTX therapy were included from a multicentre, prospective cohort study. We compared the effectiveness between starting with oral versus subcutaneous MTX over the first year. Longitudinal multivariable models, adjusted for potential baseline and time-varying confounders, were used to compare treatment changes due to inefficacy or toxicity and treatment efficacy (Disease Activity Score-28 (DAS-28), DAS-28 remission and Health Assessment Questionnaire-Disability Index (HAQ-DI)). Results: 666 patients were included (417 oral MTX, 249 subcutaneous MTX). Patients prescribed subcutaneous MTX were prescribed a higher dose of MTX (mean dose over first three months 22.3 mg vs 17.2 mg/week). At 1 year, 49% of patients initially treated with subcutaneous MTX had changed treatment compared with 77% treated with oral MTX. After adjusting for potential confounders, subcutaneous MTX was associated with a lower rate of treatment failure ((HR (95% CI) 0.55 (0.39 to 0.79)). Most treatment failures were due to inefficacy with no difference in failure due to toxicity. In multivariable models, subcutaneous MTX was also associated with lower average DAS-28 scores (mean difference (−0.38 (95% CI −0.64 to −0.10)) and a small difference in DAS-28 remission (OR 1.2 (95% CI 1.1 to 1.3)). There was no significant difference in sustained remission or HAQ-DI (p values 0.43 and 0.75). Conclusions: Initial treatment with subcutaneous MTX was associated with lower rates of treatment changes, no difference in toxicity and some improvements in disease control versus oral MTX over the first year in patients with ERA.